OPTIMALISASI PENGGUNAAN ECHOSOUNDER DALAM OLAH GERAK KAPAL DI ALUR PELAYARAN SEMPIT PADA MT. GRAND POWER - Mickel Ramadhan; Achmad Ali Mashartanto; Rizal Rochmansyah; Syafni Yelfi Siska; Kadek Laju (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The optimization of navigation equipment is very important to support maritime safety, especially when a vessel is maneuvering in narrow channels. One of the navigation instruments that plays an important role in monitoring water depth is the echosounder. This study aims to determine the procedure for using the echosounder when entering narrow shipping lanes, the factors affecting the optimization of its use, and the efforts to improve the utilization of the echosounder in supporting navigational decision making on board MT. Grand Power. This study used a descriptive qualitative method with data collection techniques including observation conducted by the researcher during the research process, interviews with the Captain, Second Officer, and Third Officer, and documentation supporting the research obtained during the researcher’s sea practice (PRALA) on board MT. Grand Power. The results of research conducted during sea practice (PRALA) show that the procedure for using the echosounder has been carried out in accordance with the ship’s standard operating procedures and the equipment manual book, which includes preparation, implementation, and evaluation stages. However, in practice there are still several factors affecting the optimal use of the instrument, such as the limited attention of the officer on watch due to dense traffic conditions, lack of continuous monitoring, and the utilization of the equipment features that has not been maximized. Efforts that can be made to improve the utilization of the echosounder include improving the competence of officers on watch, conducting routine maintenance and calibration of the equipment, and consistently implementing navigation procedures.With the optimization of echosounder usage, navigational decision making is expected to be more accurate and effective, thereby improving navigation safety, especially when the vessel operates in narrow shipping channels.